2006
DOI: 10.1002/14651858.cd001237.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Types of intra-muscular opioids for maternal pain relief in labour

Abstract: The editorial group responsible for this previously published document have withdrawn it from publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…We think that this was due to the early need for additional analgesic requirement in this group and, thus, increased opioid consumption. Several studies have determined varying rates of nausea and vomiting after the administration of meperidine [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…We think that this was due to the early need for additional analgesic requirement in this group and, thus, increased opioid consumption. Several studies have determined varying rates of nausea and vomiting after the administration of meperidine [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Our survey has shown that intramuscular pethidine is still used widely in consultant-led units (84.4% of units) despite research demonstrating its lack of efficacy as an analgesic and its adverse effects on both mother and neonate. [3][4][5][6][7]11,13,14 Since 1968 midwives have also been able to administer diamorphine via the exemption list (1968 Medicines Act). The results of one Scottish study, 9 and anecdotal evidence relating to improved analgesia with fewer side effects, have led to a renewed interest in its use.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that the dose regimens and intervals for different opioids were not related to the duration of action of the individual drugs or comparative potencies and this may have an effect on the efficacy of analgesia. 5,6,[15][16][17][18][19] This may reflect, in part, the lack of published data to suggest the most effective opioid and dosing regimen. 5,6 The dose for optimal maternal analgesia may cause excessive neonatal sedation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations